The impact of COVID-19 on labour markets and living standards in Mauritius. (December 2022) - Ranzani, Marco; Kern, Andreas
Understanding the distributional impact of the COVID-19 crisis on the labour market and ultimately on the living standards of the population is key to designing adequate policy responses to shield individuals' and families' livelihoods. This article illustrates the impact of COVID-19 on the labour market as well as on living standards in the case of a small open economy: Mauritius. We present descriptive evidence based on a unique set of telephone household surveys, representative of the Mauritian population, conducted between May 2020 and March 2021. We find that women had a higher risk of losing their job and leaving the labour force, reversing a decade-long trend of increasing labour force participation. Low-skill workers in sectors that depend on global demand – and even more so if employed informally – together with women were more likely to be affected by the crisis. One in three households reported a loss in income since the start of the pandemic, and the probability of experiencing this shock increases with the number of household members who lost their job and who were employed informally. From a policy perspective, our findings underscore the negative distributional consequences of the pandemic and provide substantive evidence for the viability of a further proactive policy stance to shield the livelihoods of vulnerable households during the economic recovery phase. JEL Codes: J21, J24, J33